Financial Performance Evaluation as a Strategy for Developing MSMEs: A Study on Arista Straike Blater Fishing - Imelda Zuliyana; Hendrajaya Hendrajaya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze financial management and its impact on the development of MSMEs, with a case study on the Arista Straike Blater Fishing business. The main focus of this study is the challenges in manual financial recording that are inefficient and risk the accuracy of financial reports, as well as how these limitations affect strategic decision-making and the sustainability of business operations. This study uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews with owners, managers, and financial staff, as well as direct observation of operational processes and interactions with customers. The analysis was carried out using a thematic approach to identify patterns in financial management and their impact on the business. The results of the study indicate that good financial management, especially in terms of cash flow control, budget planning, and financial report recording, contributes significantly to improving business operations and service quality. In addition, effective financial management supports strategic decision-making, such as investment in facilities and the introduction of new products, which contribute to increasing customer satisfaction and MSME business development. The implications of this study emphasize the importance of financial literacy for MSME owners to improve the efficiency of financial recording and reduce the risk of errors in financial reports. Key recommendations include investing in a digital recording system to improve accuracy and efficiency and financial literacy training for business actors. Further research is recommended to explore external factors that influence the effectiveness of MSME financial management, such as government regulations and access to financing.